Epitope-Based Immunome-Derived Vaccines: A Strategy for Improved Design and Safety - De Groot, Anne S. (Clinical Applications of Immunomics, 2008)
Vaccine science has extended beyond genomics to proteomics and has come to also encompass ‘immunomics,’ the study of the universe of pathogen-derived or neoplasm-derived peptides that interface with B and T cells of the host immune system. It has been theorized that effective vaccines can be developed using the minimum essential subset of T cell and B cell epitopes that comprise the ‘immunome.’ Researchers are therefore using bioinformatics sequence analysis tools, epitope-mapping tools, microarrays, and high-throughput immunology assays to discover the minimal essential components of the immunome. When these minimal components, or epitopes, are packaged with adjuvants in an appropriate delivery vehicle, the complete package comprises an epitope-based immunome-derived vaccine. Such vaccines may have a significant advantage over conventional vaccines, as the careful selection of the components may diminish undesired side effects such as have been observed with whole pathogen and protein subunit vaccines. This chapter will review the pre-clinical and anticipated clinical development of computer-driven vaccine design and the validation of epitope-based immunome-derived vaccines in animal models; it will also include an overview of heterologous immunity and other emerging issues that will need to be addressed by vaccines of all types in the future.